ROMA – BETWEEN ASCRIBED AND ASSUMED IDENTITY, A POSSIBLE MODEL FOR SUSTAINABLE INTEGRATION (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Roma - between Ascribed and Assumed Identity, A Possible Model for Sustainable Integration.The Roma community is often at the centre of many disputes and controversies. In fact, its identity hovers between an ascribed stigma  (widely and indefinitely), and a rich cultural heritage. The question of identity is complex, as it integrates cultural, social, moral,  spiritual, segregational, etc. Often, the identity of the Roma community hangs between elements assumed by its members and a  consistent effort to avoid the identity ascribed as a stigma by social factors. The present paper aims to capture this identity pendulum  of the Roma community, to identify the elements consciously assumed and those attributed to it by the collective opinion (in most of  the cases, the traits are negative and attribute a stigma to the community). Between assumed and ascribed identity, the Roma  community faces problems that society as a whole sees itself powerless to resolve or at least mitigate. Involvement on several fronts  has brought modest results, whether in economic, social or educational projects. This paper aims to present an integrated model of  progress in the social life of the Roma community.